Chromosomal microarray analysis in prenatal diagnosis: ethical considerations of the Belgian approach. Issue 2 (16th September 2019) - Muys, Joke; Blaumeiser, Bettina; Janssens, Katrien; Loobuyck, Patrick; Jacquemyn, Yves
Abstract : Detection of genetic aberrations in prenatal samples, obtained through amniocentesis or chorion villus biopsy, is increasingly performed using chromosomal microarray (CMA), a technique that can uncover both aneuploidies and copy number variants throughout the genome. Despite the obvious benefits of CMA, the decision on implementing the technology is complicated by ethical issues concerning variant interpretation and reporting. In Belgium, uniform guidelines were composed and a shared database for prenatal CMA findings was established. This Belgian approach sparks discussion: it is evidence-based, prevents inconsistencies and avoids parental anxiety, but can be considered paternalistic. Here, we reflect on the cultural and moral bases of the Belgian reporting system of prenatally detected variants.